TANTANGAN IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Riza Cameliyah (Journal of Education and Learning, 2025)
The Independent Curriculum (Curriculum Merdeka) is asolution to the needs of 21st-century education, which demands students develop critical, creative, collaborative, and characterbuilding skills. This curriculum is designed to improve the quality of learning through a student-centered approach, differentiated learning, and strengthening the Pancasila Student Profile. This study aims to identify the challenges of implementing the Independent Curriculum in improving the quality of learning in educational institutions. The method used is a descriptive qualitative approach using documentation studies of research findings, scientific articles, and relevant educational policies. Data analysis was conducted using content analysis techniques to uncover key themes related to learning quality indicators, implementation obstacles, and their impact on educational quality. The results indicate that the implementation of the Independent Curriculum has significant potential to improve student engagement, creativity, and character. However, various challenges such as limited teacher understanding, disparities in infrastructure, and minimal policy support have resulted in suboptimal implementation. Therefore, it is necessary to improve teacher competency, provide equitable educational facilities, and adapt school management so that the Independent Curriculum caneffectively improve the quality of learning in Indonesia.